The TEIViewer: Facilitating the transition from XML to web display. - Schlitz, Stephanie A.; Bodine, Garrick S. (Literary & Linguistic Computing, 2009)
This article addresses the need for TEI display tools. In order to illustrate the need for display tools, we begin with a brief review of the tools that are currently available, summarizing in particular those listed on the TEI Wiki Tools page. We then turn to a discussion of our work on the development of the TEIViewer (http://teiviewer.org), a simple, JavaScript-driven, portable display tool designed to facilitate the online representation of and interaction with elements and attributes described within select modules of the TEI P5 Guidelines and encoded as layers of data and metadata in TEI-XML documents. We explain how the TEIViewer works by describing the interactions between the XML source layer, the display layer generated via XSL, and the interactive layer powered by jQuery and CSS; and we explain why we chose the jQuery JavaScript library to manage the Viewer's functionality as well as the advantages of this decision. Finally we describe current implementations and plans for release.